Students’ Responses on Material, Comprehension, and Interaction during the English Learning Process: A Case Study at Junior High School - Nuhayani; Maulina; Nasrullah, Rahmat (Mataoleo: Journal of English Education and Linguistics, 2025)
This study aims to determine the students’ response to English learning process. The participant of this study was one class of the 8th grade students of junior high school. Data were collected in the form of classroom observations in one class and interviews with 4 students. The research design was qualitative descriptive method employing purposive sampling to choose participants. The results showed that students responded well to the English learning process, namely: learning materials, learning comprehension, learning interactions. They view an enthusiastic participation to every learning activity and learning materials delivered in the classroom as they understand topic of the lesson well. In addition to the students’ response to the comprehension of learning, most of the students’ said that they seldom find it difficult to answer the questions because they got a clear explanation from teacher before being given an assignment. In addition, responses to learning interactions, in collaborating and discussing to complete assignments, students’ give different opinions during the learning process. This study concluded that during the learning process, students showed their learning motivation and fully-participated the learning experiences. This finding will dedicate to the integrity of the way to improve students' developmental achievement in English learning.